A Preconditioned Multisplitting and Schwarz Method for Linear Complementarity Problem - Cuiyu Liu; Chen-liang Li (Journal of Applied Mathematics)
The preconditioner presented by Hadjidimos et al. (2003) can improve on the convergence rate of the classical iterative methods to solve linear systems. In this paper, we extend this preconditioner to solve linear complementarity problems whose coefficient matrix is M-matrix or H-matrix and present a multisplitting and Schwarz method. The convergence theorems are given. The numerical experiments show that the methods are efficient.